(untitled) (Development Service Industry Management, 2025)
The article examines the theoretical foundations and practical aspects of anti-crisis time management as a specialized approach to managing enterprise time resources under conditions of uncertainty. The critical importance of effective time management in the modern dynamic business environment is substantiated, where digital transformation creates new opportunities for optimizing business processes. A procedural model for the formation and implementation of time management strategies at the enterprise has been developed, which includes sequential stages of goal setting, work organization, task delegation, control, and adaptation to changes. The essence of anti-crisis time management is defined as a systematic approach aimed at timely recognition, response, and overcoming crisis phenomena through rational use of time resources. A comparative analysis of traditional and anti-crisis time management has been conducted according to key criteria: goals and priorities, planning, resources, adaptation to changes, communication, psychological burden, and risk management. It has been established that the anti-crisis approach is characterized by shorter planning horizons, higher flexibility, concentration on critically important tasks, and the need for rapid decision-making. Comprehensive strategies for improving anti-crisis time management have been proposed, including flexible strategic planning, task prioritization, instrumental support through digital systems, continuous monitoring, and formation of specialized anti-crisis teams. The practical experience of leading global companies (Toyota, Google, IKEA, P&G) in implementing effective time management systems under crisis conditions has been analyzed, confirming the practical effectiveness of the proposed approaches for ensuring stable functioning of organizations.